Culturally Responsive Pedagogy: A Systematic Overview - Manuel Caingcoy (Universidade Estadual de Alagoas, 2023)
Culturally responsive pedagogy is crucial in education, valuing diverse backgrounds to create inclusive learning environments. This paper synthesizes 32 literature sources systematically highlighting the importance of recognizing cultural backgrounds, building relationships, adapting instruction, and promoting critical consciousness. Recognition of students' backgrounds enhances academic achievement and engagement, while positive relationships foster belonging and well-being. Adapting instruction meets diverse needs and improves outcomes. Promoting critical consciousness empowers students to challenge stereotypes and address social injustices. Ongoing professional development and support are essential for effective implementation. By addressing these areas, educational institutions can create equitable and inclusive environments. Further research is needed to explore effective strategies for recognizing cultural backgrounds, investigate the impact of inclusive communities, study strategies for diverse learning needs, and examine the outcomes of promoting critical consciousness. Addressing these gaps enhances understanding and informs evidence-based practices in culturally responsive teaching.